Relationship between serum level of CD40 ligand and persistent lone atrial fibrillation - Evin Bozçalı; Veli Polat; Gönül Kutlu; Selçuk Opan; Nurcan Paker; Turgut Uygun; Barış Ökçün; Osman Karakaya (KARE Publishing, 2016)
Objective: Inflammation is thought to play a role in the pathogenesis of atrial fibrillation. The relationship between CD40 ligand (CD40L), a prothrombotic and proinflammatory molecule, and lone atrial fibrillation was presently investigated for the first time. Levels of serum CD40L were also tested, regarding potential to distinguish patients with lone atrial fibrillation from healthy individuals. Methods: Presently included were 35 patients with lone persistent atrial fibrillation and a control group of 30 healthy individuals. Serum levels of CD40L and high-sensitive C-reactive protein (hs-CRP) were measured, and transthoracic echocardiography was performed. Results: Mean serum CD40L, hs-CRP, left ventricular end-diastolic diameter, and left atrial diameter values were significantly higher in the group with lone persistent atrial fibrillation than in the control group (7.4+-3.5 ng/mL vs 4.3+-1.2 ng/mL, p<0.0001; 3.7+-1.6 mg/L vs 1.7+-0.8 mg/L, p<0.0001; 53.0+-4.2 mm vs 46.0+-3.8, p<0.0001; 43.5+-3.5 mm vs 33.7+-3.5, p<0.0001, respectively). Serum CD40L levels were positively correlated with left atrial diameter (r=0.81, p<0.0001) and hs-CRP (r=0.72, p<0.0001). Receiver operating characteristic curve analysis revealed that serum CD40L at the optimal cut-off level of >4.5 ng/mL successfully discriminated patients with lone atrial fibrillation from controls (area under the curve: 0.847; 95% confidence interval: 0.759-0.934; p<0.0001). Conclusion: The present findings suggest that CD40L levels play a crucial role in the development of lone atrial fibrillation. In addition, results support that regular clinical follow-up of these patients is necessary, due to increased cardiovascular disease risk, determined by elevated CD40L levels.